Text-image watermarking based on integer wavelet transform (IWT) and discrete cosine transform (DCT) - Reem A. Alotaibi; Lamiaa A. Elrefaei (Applied Computing and Informatics, 2019)
Text-images still have a great importance, despite the spread of electronic texts. Text-images are protected using digital watermarking. This paper proposes a watermarking method applied to text-images. This method integrates two transforms: integer wavelet transform (IWT) and discrete cosine transform (DCT). For the watermark embedding, IWT is performed on the cover image and DCT is applied to the low frequency sub-band LL. The watermark image is inserted in the lower to medium DCT coefficients to achieve a high degree of robustness and imperceptibility. Experiments using different Arabic text-images are performed to evaluate the proposed method in terms of imperceptibility and robustness. Results show that the proposed method has higher imperceptibility compared to other existing methods applied to Arabic text-images. Also, the proposed method provides good robustness results, especially against compression and noise. Keywords: Watermarking, IWT, DCT, PSNR